Molecular Cloning and Subcellular Localization of Tektin2-Binding Protein 1 (Ccdc 172) in Rat Spermatozoa. (April 2014) - Yamaguchi, Airi; Kaneko, Takane; Inai, Tetsuichiro; Iida, Hiroshi
Tektins (TEKTs) are composed of a family of filament-forming proteins localized in cilia and flagella. Five types of mammalian TEKTs have been reported, all of which have been verified to be present in sperm flagella. TEKT2, which is indispensable for sperm structure, mobility, and fertilization, was present at the periphery of the outer dense fiber (ODF) in the sperm flagella. By yeast two-hybrid screening, we intended to isolate flagellar proteins that could interact with TEKT2, which resulted in the isolation of novel two genes from the mouse testis library, referred as a TEKT2-binding protein 1 (TEKT2BP1) and -protein 2 (TEKT2BP2). In this study, we characterized TEKT2BP1, which is registered as a coiled-coil domain-containing protein 172 (Ccdc172) in the latest database. RT-PCR analysis indicated that TEKT2BP1 was predominantly expressed in rat testis and that its expression was increased after 3 weeks of postnatal development. Immunocytochemical studies discovered that TEKT2BP1 localized in the middle piece of rat spermatozoa, predominantly concentrated at the mitochondria sheath of the flagella. We hypothesize that the TEKT2-TEKT2BP1 complex might be involved in the structural linkage between the ODF and mitochondria in the middle piece of the sperm flagella.